If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7(12) + -15 = 0 Multiply -7 * 12 5 + -84 + -15 = 0 Combine like terms: 5 + -84 = -79 -79 + -15 = 0 Combine like terms: -79 + -15 = -94 -94 = 0 Solving -94 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(m-6)=6(m-1) | | (3+5i)(2+3i)(7+4i)=0 | | -2(X-4)+5x=2(X+3)+X+3 | | 5x^2-9x-2=o | | 2x+4-5=3x+1 | | 5[8+(81)]= | | f+12=4 | | f+12=-4 | | 6x-3(7-2x)=14 | | 5-7.12-15= | | (9(m+5)-15)+(2(m-3)+4)= | | 6(7au)+u=36+u | | 3x-3(5-2x)=3 | | 8a^3+27b^3+64c^3=72abc | | 9(2X-1)=3(3x+3) | | 1p+2=-1 | | 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 |